2012
DOI: 10.1590/s1806-37132012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Broncoscopia no diagnóstico de tuberculose pulmonar em pacientes com baciloscopia de escarro negativa

Abstract: Objective: To evaluate the diagnostic accuracy of bronchoscopy in patients with clinical or radiological suspicion of tuberculosis who were unable to produce sputum or with negative sputum smear microscopy results. Methods: A prospective cross-sectional study involving 286 patients under clinical or radiological suspicion of having pulmonary tuberculosis and submitted to bronchoscopy-BAL and transbronchial biopsy (TBB). The BAL specimens were submitted to direct testing and culture for AFB and fungi, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
(15 reference statements)
1
14
1
2
Order By: Relevance
“…This study was in concordance with a study done by Jacomelli M et al in which out of 286 cases who underwent bronchoscopy, 127 cases were diagnosed on bronchoscopic findings as pulmonary tuberculosis. 11 On comparing the top two suspected clinical diagnoses of pulmonary tuberculosis and lung malignancy with the findings during bronchoscopy, it was observed that the highest proportion (80 cases) of normal bronchoscopy findings were noted in subjects with "suspected pulmonary tuberculosis" category which was in concordance with the study done by Rahul Magazine et al who had 51.9% cases showing normal bronchoscopic findings in subjects with suspected pulmonary tuberculosis. 12 Endobronchial growth was the next common finding followed by external compression.…”
Section: Discussionsupporting
confidence: 84%
“…This study was in concordance with a study done by Jacomelli M et al in which out of 286 cases who underwent bronchoscopy, 127 cases were diagnosed on bronchoscopic findings as pulmonary tuberculosis. 11 On comparing the top two suspected clinical diagnoses of pulmonary tuberculosis and lung malignancy with the findings during bronchoscopy, it was observed that the highest proportion (80 cases) of normal bronchoscopy findings were noted in subjects with "suspected pulmonary tuberculosis" category which was in concordance with the study done by Rahul Magazine et al who had 51.9% cases showing normal bronchoscopic findings in subjects with suspected pulmonary tuberculosis. 12 Endobronchial growth was the next common finding followed by external compression.…”
Section: Discussionsupporting
confidence: 84%
“…gov.br/DATASUS/index.php, acessado em 15/ Jul/2013). Os sinais e sintomas evidentes podem confundir o diagnóstico, até mesmo com imagens radiológicas compatíveis 15 . Por isso, exames bacteriológicos, como a baciloscopia e a cultura, acopladas ou não à broncoscopia ou à biopsia, são exames que devem ser utilizados para a confirmação diagnóstica.…”
Section: Discussionunclassified
“…In Brazil, Jacomelli and co-workers [52] investigated 286 patients with clinical or radiological suspicion of TB who were unable to produce sputum or had a negative smear. They found that 7% of infections were caused by Pneumocystis , fungi and Nocardia .…”
Section: Discussionmentioning
confidence: 99%